The Effects Of Verbal Problem Solving Instruction On Students' Structuring Acquisition and Retention Of Knowledge In Methods Of Cooking - Ahmad Shah, Aliah (2005)
The purpose of this study is to examine the effects of teaching verbal problem solving to students' structuring, acquisition and retention of knowledge in Methods of Cooking. The study is carried out on 148 students from two classes each of Catering Technology (n=77) and Food Management (n=71). Taken as intact, the classes are randomly assigned into two experiment (n=37; n=35) and two control (n=40; n=36) groups. Using a quasi-experimental of non-equivalent control group of pretest, posttest and delayed posttest design, 10 treatment of teaching using verbal problem solving is given for a duration of 40 minutes of classroom teaching for four weeks. For the pretest, posttest and delayed posttest, parallel achievement tests are used to demonstrate the amount of knowledge acquired and retained after the treatment. A concept mapping test is used to assess the knowledge structure of the students before